Revisiting Organizational Dynamics in Education: A Theoretical Approach to Leadership, Satisfaction, Commitment, and Performance - Purwatiningsih Purwatiningsih; Achmad Husen; Suparno Suparno (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to analyze the relationship between leadership style, job satisfaction, organizational commitment, and teacher performance in the education sector. The results of the study show that transformational leadership style plays a significant role in increasing job satisfaction and organizational commitment of teachers. This relationship ultimately has a positive impact on teacher performance. Through an in-depth literature review using trusted academic sources such as Google Scholar and Scopus, it was found that the combination of supportive leadership, high job satisfaction, and strong organizational commitment creates a conducive and productive work environment. This study recommends the implementation of empowering leadership styles as well as strategies that focus on increasing teacher satisfaction and commitment to support the achievement of educational goals.